Detection of bovine herpesvirus 2 and bovine herpesvirus 4 DNA in trigeminal ganglia of naturally infected cattle by polymerase chain reaction - Campos, Fabrício Souza; Franco, Ana Cláudia; Oliveira, Martha Trindade; Firpo, R.M.; Strelczuk, G.; Fontoura, F.E.; Kulma, Marcos Iuri Roos; Maidana, Silvina Soledad; Romera, Sonia Alejandra; Spilki, Fernando; Silva, Alessandra D. Avila; Hübner, Sílvia De Oliveira; et al. (Elsevier, 2019)
Establishment of latent infection within specific tissues in the host is a common biological feature of the herpesviruses. In the case of bovine herpesvirus 2 (BoHV-2), latency is established in neuronal tissues, while bovine herpesvirus 4 (BoHV-4) and ovine herpesvirus 2 (OvHV-2) latent virus targets on cells of the monocytic lineage. This study was conducted in quest of BoHV-2, BoHV-4 and OvHV-2 DNA in two hundred trigeminal ganglia (TG) specimens, derived from one hundred clinically healthy cattle, majority of them naturally infected with bovine herpesvirus 1 (BoHV-1) and bovine herpesvirus 5 (BoHV-5). Total DNA extracted from ganglia was analyzed by polymerase chain reaction (PCR) designed to amplify part of the genes coding for BoHV-2, and BoHV-4 glycoprotein B and, for OvHV-2, the gene coding for phosphoribosylformylglycinamidine synthase-like protein. BoHV-2 DNA was detected in TG samples of two (2%) and BoHV-4 DNA in nine (9%) of the animals, whereas OvHV-2 DNA could not be detected in any of the TG DNA. The two animals in which BoHV-2 DNA was identified were also co-infected with BoHV-1 and BoHV-5. Within the nine animals in which BoHV-4 DNA was detected, six were also co-infected with BoHV-1 and BoHV-5. This report provides for the first time evidence that viral DNA from BoHV-2 and BoHV-4 can be occasionally detected in TG of naturally infected cattle. Likewise, in this report we provided for the first time evidence that the co-infection of cattle with three distinct bovine herpesviruses might be a naturally occurring phenomenon.